Modified concrete, method of preparation and use

CN122541158BActive Publication Date: 2026-10-16NINGXIA ELECTRIC POWER CONSTR PROJECT CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611048762.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-15
Publication Date
2026-10-16
Estimated Expiration
2046-07-15

AI Technical Summary

Technical Problem

[0004]本申请要实现的技术效果是:提供一种改性混凝土、制备方法及应用,解决现有技术中制作水泥电杆时容易发生分层和偏析,导致电杆截面材质分布不均,影响力学性能的均一性的技术问题

Benefits of technology

1. 本申请提供的方案通过采用N-异丙基丙烯酰胺与2-丙烯酰胺-2-甲基丙磺酸的共聚物作为粘度改性剂,该共聚物分子链中的N-异丙基丙烯酰胺单元具有温度响应特性,分子链中的2-丙烯酰胺-2-甲基丙磺酸单元以磺酸基团提供强耐碱性和钙离子耐受性,2-丙烯酰胺-2-甲基丙磺酸的摩尔含量控制在10%-20%,在该范围内,磺酸基团的含量既能确保共聚物在pH>13的水泥孔隙液和富含Ca2+的环境中保持结构稳定和相转变行为的可逆性,又不会因磺酸基团含量过高而导致共聚物亲水性过强、相转变温度过高或相转变行为消失,从而有效抑制离心力场下颗粒径向偏析和纤维差异沉降。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a modified concrete, a preparation method and application. The concrete comprises Portland cement, mineral admixtures, fiber materials and the like, and uses N-isopropyl acrylamide and 2-acrylamide-2-methylpropanesulfonic acid copolymer as a viscosity modifier, wherein the molar content of 2-acrylamide-2-methylpropanesulfonic acid is 10%-20%. The modified concrete disclosed by the application utilizes the temperature-sensitive phase change characteristics of the copolymer, and cooperates with specific temperature-controlled mixing and preheating pipe mold centrifugal process, so that the differential settlement of the fiber and the aggregate is effectively inhibited in the forming, and the problem of uneven material distribution of the pole section is solved. The application also provides a corresponding preparation method and application in manufacturing cement poles, and significantly improves the mechanical property uniformity, crack resistance and durability of the pole.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of concrete preparation technology, and more specifically, relates to a modified concrete, its preparation method, and its application. Background Technology

[0002] Cement poles are key supporting components for power transmission and distribution lines and communication lines, and their mechanical properties and durability directly affect the safe operating life of the lines. Traditional cement poles are typically composed of silicate cement, aggregates, water, and a steel reinforcement cage. This structural form can meet general load-bearing requirements, but in actual production and use, it suffers from poor crack resistance and corrosion resistance. To improve the overall performance of cement pole concrete, existing technologies often use multi-mineral admixtures (such as slag, fly ash, and silica fume) to replace part of the cement and introduce fiber materials to enhance crack resistance. However, the density, elastic modulus, and geometric dimensions of different admixtures and fiber materials vary greatly, which can easily lead to delamination and segregation during the manufacture of cement poles, resulting in uneven material distribution in the pole cross-section and affecting the uniformity of mechanical properties.

[0003] To address the issue of differential settlement, existing technologies often incorporate viscosity modifiers. For instance, Chinese patent CN121248257A discloses a prestressed tailings concrete pole and its manufacturing method, using modified iron tailings as the main aggregate, combined with various mineral admixtures and fiber materials. A hydroxyethyl cellulose and venetanol composite system is used as a viscosity modifier to improve the cohesiveness and anti-bleeding ability of the mixture. However, this conventional viscosity modification system still faces some drawbacks in actual cement pole molding. On one hand, cement hydration releases a large amount of calcium hydroxide, making the system highly alkaline and rich in calcium ions. Conventional cellulose ethers and natural high-molecular-weight polysaccharides (such as venetanol) are prone to molecular chain hydrolysis and degradation or salting-out precipitation in this high-alkaline, high-calcium environment, leading to a decline or even failure of their thickening and cohesive properties over time. On the other hand, under the action of the forming force field, in order to achieve the effect of maintaining material uniformity and suppressing the differential settlement of high-density fibers and coarse aggregates, it is necessary to significantly increase the amount of such conventional viscosity modifiers. This can easily cause the concrete to have excessively high viscosity and extremely poor fluidity during initial mixing and pouring, which not only increases the difficulty of construction and placement, but also easily introduces microscopic air bubbles and voids that are difficult to remove into the poles. If the amount of these modifiers is reduced in order to ensure the fluidity of the concrete, the segregation of aggregates and fibers under the action of gravity and strong forming shear force during the forming process cannot be effectively controlled. Summary of the Invention

[0004] The technical effect to be achieved by this application is to provide a modified concrete, a preparation method and an application, to solve the technical problem in the prior art that the production of cement poles is prone to delamination and segregation, resulting in uneven material distribution in the pole cross section and affecting the uniformity of mechanical properties.

[0005] To achieve the above-mentioned technical effects, this application provides a modified concrete, comprising the following components by weight: 350-450 parts silicate cement, 200-280 parts calcined coal gangue powder, 150-220 parts metakaolin, 15-25 parts nano silica sol, 120-180 parts limestone powder, 400-500 parts slag, 0.1-0.5 parts nano silica dispersant, 3-8 parts viscosity modifier, 17-33 parts fiber material, 5-10 parts polycarboxylate superplasticizer, and 342-571 parts mixing water; The viscosity modifier is a copolymer of N-isopropylacrylamide and 2-acrylamide-2-methylpropanesulfonic acid, wherein the molar content of 2-acrylamide-2-methylpropanesulfonic acid is 10%-20%.

[0006] Furthermore, the fiber material comprises 12-20 parts steel fiber, 3-8 parts basalt fiber, and 2-5 parts PVA fiber; The steel fibers have a length of 8-12 mm and a diameter of 0.15-0.20 mm; the basalt fibers have a length of 6-12 mm and a diameter of 10-17 μm; and the PVA fibers have a length of 4-8 mm and a diameter of 20-40 μm.

[0007] Furthermore, the steel fiber is a steel fiber treated with NDZ-201 titanate coupling agent, and the amount of NDZ-201 titanate coupling agent is 0.3-0.8% of the mass of the steel fiber; The basalt fiber and PVA fiber are basalt fiber and PVA fiber treated with KH-550 silane coupling agent, respectively, and the amount of KH-550 silane coupling agent is 0.8-1.5% of the total mass of basalt fiber and PVA fiber.

[0008] Furthermore, the silica particles in the nano silica sol have a diameter of 20-50 nm and a solid content of 20-30 wt%.

[0009] Furthermore, the calcined coal gangue powder is calcined coal gangue powder that has been impregnated with 5-10wt% dilute sulfuric acid for 2-4 hours, washed with water until neutral, and then dried.

[0010] To achieve the above-mentioned technical effects, this application also provides a method for preparing modified concrete, wherein the modified concrete includes the modified concrete described in any one of the above claims, and the method includes: The calcined coal gangue powder, metakaolin, limestone powder, slag and silicate cement in the formula are thoroughly mixed to obtain dry mix; The viscosity modifier, polycarboxylate superplasticizer, and mixing water were mixed in the specified amounts, and nano-silica sol dispersed by nano-silica dispersant was added to obtain a liquid phase system. The dry mixture is added to the liquid system and stirred. Fiber materials are added in batches and stirring is continued to obtain a modified concrete mixture. The temperature of the mixing water is controlled at 35-40℃, and the outlet temperature of the modified concrete mixture is controlled at 32-36℃.

[0011] To achieve the above-mentioned technical effects, this application also provides the application of the modified concrete described in any one of the above claims or the preparation method of the modified concrete described above in the manufacture of cement poles, including: The mixture of the modified concrete is fed into a preheated pipe mold; The tube mold is centrifuged and formed; After centrifugal molding, the material is steam cured and then demolded to obtain cement poles.

[0012] Furthermore, the preheating temperature of the tube mold is 40-45℃.

[0013] Furthermore, the centrifugal molding adopts a three-stage centrifugal molding process, which includes, in sequence: During the low-speed fabric feeding stage, the rotation speed is 80-120 rpm and the time is 2-3 minutes; During the medium-speed compaction stage, the rotation speed is 200-350 rpm and the time is 3-5 minutes; During the high-speed finishing stage, the rotation speed is 450-600 rpm and the time is 5-8 minutes.

[0014] Furthermore, the steam curing includes: After standing at 25-30℃ for 2-3 hours, the temperature is increased from 30℃ to 60-70℃ at a rate of 10-15℃ / h. Steam curing is carried out at a constant temperature of 60-70℃ for 4-6 hours, and then cooled from 60-70℃ to room temperature at a cooling rate of no more than 10℃ / h to complete the steam curing process. The beneficial effects of this application are as follows: 1. The solution provided in this application uses a copolymer of N-isopropylacrylamide and 2-acrylamide-2-methylpropanesulfonic acid as a viscosity modifier. The N-isopropylacrylamide unit in the copolymer molecular chain exhibits temperature-responsive characteristics, while the 2-acrylamide-2-methylpropanesulfonic acid unit provides strong alkali resistance and calcium ion tolerance through its sulfonic acid groups. The molar content of 2-acrylamide-2-methylpropanesulfonic acid is controlled at 10%-20%. Within this range, the content of sulfonic acid groups ensures that the copolymer can withstand cement pore liquids with pH > 13 and calcium-rich environments. 2+It maintains structural stability and reversibility of phase transition behavior in the environment, and will not cause excessive hydrophilicity, excessive phase transition temperature or disappearance of phase transition behavior of copolymer due to excessive sulfonic acid group content, thereby effectively suppressing radial segregation of particles and differential sedimentation of fibers under centrifugal force field.

[0015] 2. In the preparation process of modified concrete, this application controls the temperature of the mixing water to 35-40℃ and the temperature of the mixture exiting the mixer to 32-36℃, so that the initial temperature of the mixture is close to the lower limit of the phase transformation temperature of the viscosity modifier. This creates the preconditions for reliably triggering the phase transformation and thickening during the subsequent centrifugal molding process. No additional external heating equipment is required. The phase transformation can be self-triggered by relying solely on the shear heating of the centrifugal process itself and the heat transfer of the mold.

[0016] 3. In the manufacture of cement poles, this application involves feeding the mixture into a preheated mold and centrifuging it. The preheating temperature of the mold is 40-45℃, which, combined with the initial temperature of the mixture of 32-36℃, makes the temperature of the mixture after entering the mold closer to the phase transition temperature range. Then, during the centrifugal molding stage, the system temperature crosses the phase transition temperature through heat transfer from the mold and shear heating, thereby achieving the effects of viscosity increase, suppression of segregation, and fiber sedimentation. Detailed Implementation

[0017] The embodiments of the technical solution of this application will be described in detail below. The following embodiments are only used to illustrate the technical solution of this application more clearly, and are therefore only examples, and should not be used to limit the scope of protection of this application.

[0018] One embodiment of this application provides a modified concrete, comprising the following components by weight: 350-450 parts silicate cement, 200-280 parts calcined coal gangue powder, 150-220 parts metakaolin, 15-25 parts nano silica sol, 120-180 parts limestone powder, 400-500 parts slag, 0.1-0.5 parts nano silica dispersant, 3-8 parts viscosity modifier, 17-33 parts fiber material, 5-10 parts polycarboxylate superplasticizer, and 342-571 parts mixing water; The viscosity modifier is a copolymer of N-isopropylacrylamide and 2-acrylamide-2-methylpropanesulfonic acid, and the molar content of 2-acrylamide-2-methylpropanesulfonic acid is 10%-20%.

[0019] Specifically, among the components mentioned above, silicate cement serves as the primary cementing material, providing early strength and hydration products. In some examples of this application, P.I. 52.5 grade silicate cement is used, with a strength grade of 52.5, which provides sufficient early and late strength for the pole concrete.

[0020] Calcined coal gangue powder, metakaolin, nano silica sol, limestone powder and slag are used as functional mineral admixtures and are compounded with silicate cement to form a multi-graded system.

[0021] Among them, calcined coal gangue powder is an active mineral admixture obtained by grinding coal gangue after high-temperature calcination, with an Al2O3 content of 15-30% and a specific surface area ≥400m². 2 / kg, with a particle size D50 of 20-40 μm. The calcination process dehydroxylates the kaolinite in the coal gangue, transforming it into metakaolinite, thus imparting pozzolanic activity. In some examples of this application, the calcined coal gangue powder is impregnated with 5-10 wt% dilute sulfuric acid for 2-4 hours, washed with water until neutral, and dried before use. The dilute sulfuric acid impregnation dissolves the vitreous coating on the surface of the coal gangue powder, increasing the specific surface area and exposing more active silica-alumina sites, while simultaneously dissolving some soluble metal ions, significantly enhancing the pozzolanic activity of the coal gangue powder.

[0022] Metakaolin is an amorphous silica-alumina compound formed by calcining kaolinite at 600-800℃ to remove hydroxyl groups. It has an Al₂O₃ content ≥45%, SiO₂ content ≥50%, a particle size D50 of 2-5 μm, and a 28-day pozzolanic activity index ≥80%. The active silica-alumina in metakaolin reacts with calcium hydroxide released during early cement hydration in a pozzolanic reaction, generating additional CSH gel and CAH gel. Simultaneously, it consumes calcium hydroxide, refines pores, and increases matrix density.

[0023] The nano-silica sol contains silica particles with a diameter of 20-50 nm, a solid content of 20-30 wt%, and a pH of 9-10. Nano-silica exhibits extremely high pozzolanic activity, rapidly reacting with calcium hydroxide in the early stages to form CSH gel. Simultaneously, its nanoparticles fill the nanopores between cement particles, significantly improving the matrix density. Due to the extremely large specific surface area of ​​nano-silica, direct addition easily leads to agglomeration; therefore, it must be used in conjunction with a nano-silica dispersant. The nano-silica dispersant is a polycarboxylate type dispersant, such as sodium / ammonium salts, used at a dosage of 0.1-0.5 parts. It prevents the agglomeration of nano-silica particles through steric hindrance and electrostatic repulsion, ensuring its uniform dispersion in the liquid phase system.

[0024] The limestone powder has a CaCO3 content ≥95% and a particle size D50 of 8-15 μm. As a microfiller, limestone powder fills the gaps between cement particles and mineral admixture particles, providing nucleation sites to accelerate cement hydration and participating in the reaction of calcium aluminate carboxylate to generate additional hydration products. The addition of limestone powder also improves the particle size distribution of the mixture and reduces porosity.

[0025] The slag used is granulated blast furnace slag powder of grade S95 or above, with a specific surface area ≥400 m². 2 / kg, 7-day activity index ≥75%. As a high-volume mineral admixture, slag undergoes a hydration reaction in the alkaline environment provided by cement hydration, generating CSH gel, which mainly contributes to mid-to-late-stage strength. The addition of slag reduces cement usage, decreases hydration heat and the risk of temperature cracking, while simultaneously improving durability.

[0026] The viscosity modifier is a copolymer of N-isopropylacrylamide (NIPAM) and 2-acrylamide-2-methylpropanesulfonic acid (AMPS), with AMPS molar content ranging from 10% to 20%. This copolymer exhibits thermosensitive phase transition characteristics, and its lowest critical solution temperature (LCST) is provided by the NIPAM segments. The sulfonic acid groups introduced by the AMPS segments enhance the stability of the copolymer in high-alkali and high-calcium environments through steric hindrance and electrostatic repulsion effects.

[0027] Specifically, the LCST of NIPAM homopolymer is approximately 32°C. However, in cement pore liquid with pH > 13 and rich in calcium ions, the amide groups on the NIPAM homopolymer molecular chains are prone to hydrolysis, and the coordination of calcium ions with the amide groups leads to salting-out precipitation of the molecular chains, causing a significant drift in LCST and even loss of temperature-sensitive properties. This application introduces AMPS comonomer. The sulfonic acid groups of AMPS have strong hydrophilicity and alkali resistance. On the one hand, they prevent calcium ions from approaching the amide groups through electrostatic repulsion; on the other hand, they protect the amide groups from hydrolytic attack through steric hindrance, thus controlling the LCST drift of the copolymer within 5°C in cement pore liquid. The temperature-sensitive phase transition behavior of this copolymer is as follows: when the system temperature is below the LCST, the copolymer molecular chains are in a stretched hydrated state, and the viscosity of the mixture is low, ensuring fluidity during the initial mixing and distribution stages; when the system temperature is above the LCST, the copolymer molecular chains undergo hydrophobic shrinkage and form a physical cross-linked network, increasing the viscosity of the mixture and effectively suppressing differential sedimentation between high-density steel fibers and cement paste under the action of centrifugal force. The phase transition is reversible; when the temperature drops below LCST, the copolymer molecular chains stretch out again, and the viscosity recovers.

[0028] In some examples of this application, the fiber material includes 12-20 parts of steel fiber, 3-8 parts of basalt fiber, and 2-5 parts of PVA fiber; The steel fibers are 8-12 mm in length, 0.15-0.20 mm in diameter, with a diameter-to-length ratio of 40-60, and a tensile strength ≥1200 MPa. The steel fibers bridge macroscopic cracks at the macroscopic scale (>1 mm), improving bending toughness. This application uses shorter steel fibers (8-12 mm), which, compared to conventionally long fibers (30-60 mm), exhibit less difference in centrifugal settling velocity, making them more suitable for centrifugal forming processes.

[0029] The basalt fibers are 6-12 mm in length and 10-17 μm in diameter. Basalt fibers can intercept mesoscopic cracks in the mesoscopic scale (0.1-1 mm), and their alkali resistance and high temperature resistance make them stable in cement pore fluid for a long time.

[0030] PVA fibers are 4-8 mm in length, 20-40 μm in diameter, and have an elongation of ≥6%. PVA fibers bridge microcracks and inhibit plastic shrinkage at the microscale (<0.1 mm). The hydrophilicity of PVA fibers ensures good compatibility with cementitious matrices and results in high interfacial bond strength.

[0031] To improve the interfacial bonding strength between the fiber and the cement matrix, this embodiment applies differentiated coupling agent treatments to the three types of fibers.

[0032] Steel fibers are treated with NDZ-201 titanate coupling agent, with the amount of NDZ-201 being 0.3-0.8% of the steel fiber mass. The alkoxy group at one end of the NDZ-201 titanate coupling agent molecule forms Fe-O-Ti coordination bonds with the iron oxides on the steel fiber surface, while the organic long chain at the other end forms mechanical interlocking with the CSH gel, a cement hydration product. This interfacial bonding mechanism creates a chemical anchor between the steel fiber and the matrix, significantly improving the interfacial bond strength. Basalt fibers and PVA fibers are treated with KH-550 silane coupling agent, with the amount of KH-550 being 0.8-1.5% of the total mass of the basalt fibers and PVA fibers. After hydrolysis, the alkoxy group at one end of the KH-550 silane coupling agent condenses with the silanol groups on the surface of the basalt fibers and PVA fibers to form Si-O-Si covalent bonds, while the amino group at the other end forms hydrogen bonds or ionic bonds with the CSH gel. This interfacial bonding mechanism enables basalt fibers and PVA fibers to form covalent bonds anchoring them to the matrix. When the KH-550 dosage is below 0.8%, the interfacial bonding is insufficient; when the dosage is above 1.5%, the excess coupling agent forms a weak interfacial layer on the fiber surface.

[0033] One embodiment of this application provides a method for preparing modified concrete, wherein the modified concrete includes the modified concrete described in the above embodiments, and the preparation method includes the following steps: Step S1: Thoroughly mix the calcined coal gangue powder, metakaolin, limestone powder, slag and silicate cement according to the formula to obtain dry mix; In this step, all powder components are mixed evenly in a dry state to avoid clumping caused by different wetting rates of the components after water is added later. The mixing time is generally 2-4 minutes, until all components are uniform in color and there are no visible clumps.

[0034] Step S2: Mix the viscosity modifier, polycarboxylate superplasticizer and mixing water according to the formula, and add the nano silica sol dispersed by the nano silica dispersant to obtain a liquid phase system; In this step, the temperature of the mixing water is controlled at 35-40℃. The viscosity modifier and polycarboxylate superplasticizer are first dissolved in the mixing water to ensure that they are fully dissolved and uniformly dispersed; the nano-silica sol is pre-dispersed with a nano-silica dispersant to prevent the nanoparticles from agglomerating before being added to the liquid phase system.

[0035] The reason for controlling the mixing water temperature at 35-40℃ is that this temperature range is close to but lower than the LCST of the viscosity modifier, so that the viscosity modifier remains in a low viscosity state in the liquid phase system, which is convenient for subsequent mixing with the dry mix; at the same time, this temperature provides heat reserve for the subsequent outlet temperature of the mixture (32-36℃), making up for the heat loss during the mixing process of the dry mix.

[0036] Step S3: Add the dry mix to the liquid phase system and stir. Add the fiber material in batches and continue stirring to obtain the modified concrete mixture.

[0037] In this step, the dry mixture is first added to the liquid phase system and stirred for 2-3 minutes to fully wet and disperse the powder; then the fiber material is added in batches, first steel fiber is added and stirred for 1-2 minutes, then basalt fiber and PVA fiber are added and stirred for 1-2 minutes to ensure that each fiber is evenly dispersed.

[0038] The purpose of adding fibers in batches is to avoid clumping caused by adding all three types of fibers simultaneously. The outlet temperature of the modified concrete mixture is controlled at 32-36℃, which is only 2-16℃ different from the LCST (Limited Time Limit), providing a temperature basis for triggering the thermosensitive phase transition during subsequent centrifugal molding. When the outlet temperature is below 32℃, it is difficult to trigger the phase transition during centrifugation; when the outlet temperature is above 36℃, it may exceed the LCST, causing the mixture to undergo premature phase transition and become viscous during transportation or distribution, affecting the flowability of the material.

[0039] The modified concrete or its preparation method described in the above embodiments can be applied to the manufacture of cement poles, specifically including the following steps: Step A1: The modified concrete mixture is fed into a preheated pipe mold; Preferably, the preheating temperature of the mold is 40-45℃. The purpose of preheating the mold is twofold: firstly, to allow the temperature of the mixture to rise further through heat conduction when the mixture is poured into the mold, thus compensating for heat loss during transportation; secondly, the preheating temperature is close to or slightly higher than the LCST, ensuring that the mixture is in a state close to the phase change temperature immediately after being poured into the mold, providing a temperature basis for reliably triggering the phase change during subsequent centrifugation.

[0040] Step A2: Centrifuge the tube mold; Preferably, this step can adopt a three-stage centrifugal molding process, which includes a low-speed feeding stage, a medium-speed compaction stage, and a high-speed finishing stage. Low-speed feeding stage: rotation speed is 80-120 rpm, time is 2-3 min. In this stage, the temperature of the mixture rises from 32-36℃ when it enters the mold to 35-38℃ through heat conduction in the tube mold, which is still lower than LCST. The mixture remains in a low-viscosity state and is evenly distributed along the tube mold wall under the action of low-speed centrifugal force. Medium-speed compaction stage: rotation speed is 200-350 rpm, time is 3-5 min. In this stage, centrifugal shear heating causes the temperature of the mixture to rise from 35-38℃ to 38-45℃, crossing the LCST threshold. The viscosity modifier undergoes a thermosensitive phase transition, and the viscosity of the mixture increases sharply, forming a high-viscosity locked state, which effectively inhibits the differential sedimentation between high-density steel fibers and cement paste. High-speed finishing stage: rotation speed is 450-600 rpm, time is 5-8 min. In this stage, the temperature of the mixture is stabilized at 42-48℃, which is higher than LCST, and it maintains a high viscosity locked state. Under the action of high-speed centrifugal force, it completes compaction and structural homogenization, and removes residual air bubbles.

[0041] Step A3: After centrifugal molding, steam curing is performed, and the cement pole is demolded to obtain the cement pole.

[0042] Preferably, steam curing employs a gradient steam curing method, including: static curing at 25-30℃ for 2-3 hours; this stage allows the cement to complete initial hydration, establishing a skeletal structure and preventing structural damage due to incomplete formation of hydration products during subsequent heating; subsequently, heating from 30℃ to 60-70℃ at a rate of 10-15℃ / h. This stage temperature is significantly higher than LCST, maintaining the polymer in a high-viscosity state and accelerating matrix hydration. The heating rate is controlled at 10-15℃ / h because this rate matches the pozzolanic reaction kinetics of slag and metakaolin, avoiding temperature stress cracking due to excessively rapid heating. Then, constant temperature curing at 60-70℃ for 4-6 hours. This stage activates the mid-to-late stage pozzolanic reaction of slag and metakaolin, generating additional CSH gel and CAH gel, improving matrix density and strength. Finally, cooling from 60-70℃ to room temperature at a rate not exceeding 10℃ / h. This stage controls the cooling rate to avoid temperature stress cracking. Simultaneously, once the temperature drops below the LCST (lowest temperature limit), the polymer molecular chains relax and regain flexibility, releasing residual stress. When the cooling rate exceeds 10℃ / h, excessive temperature stress can easily lead to cracking.

[0043] After steam curing, the concrete poles are demolded.

[0044] The present invention will now be described with reference to specific embodiments and comparative examples.

[0045] In the following examples and comparative examples, P·I 52.5 grade silicate cement was used; the specific surface area of ​​the calcined coal gangue powder was ≥400 m². 2 / kg, particle size D50=20-40μm, Al2O3 content 15-30%; metakaolin with Al2O3 content ≥45%, SiO2 content ≥50%, particle size D50=2-5μm, 28d pozzolanic activity index ≥80%; nano silica sol with silica particle size 20-50nm, pH value 9-10; limestone powder with CaCO3 content ≥95%, particle size D50=8-15μm; slag is S95 grade granulated blast furnace slag powder with specific surface area ≥400m². 2 / kg; the polycarboxylate superplasticizer is DS-J2 retarded polycarboxylate high-performance superplasticizer with a solid content ≥20% and a water reduction rate ≥25%; the nano silica dispersant is sodium polycarboxylate dispersant NOPCO SN-5040.

[0046] Example 1 This embodiment provides a modified concrete with the following formula by weight: 400 parts silicate cement, 240 parts calcined coal gangue powder (impregnated with 8wt% dilute sulfuric acid for 3 hours, washed with water to neutral and dried), 180 parts metakaolin, 20 parts nano silica sol (solid content 25%), 150 parts limestone powder, 450 parts slag, 0.3 parts nano silica dispersant, 4 parts viscosity modifier, 16 parts steel fiber, 5 parts basalt fiber, 3 parts PVA fiber, 8 parts polycarboxylate superplasticizer, and 432 parts mixing water.

[0047] The viscosity modifier is a copolymer of N-isopropylacrylamide and 2-acrylamide-2-methylpropanesulfonic acid, with a molar content of 15% for 2-acrylamide-2-methylpropanesulfonic acid. The LCST of this copolymer in cement pore liquid is approximately 44℃ (drift ≤3℃). The steel fibers are 10mm long and 0.18mm in diameter, treated with NDZ-201 titanate coupling agent at a dosage of 0.5% of the steel fiber mass. The basalt fibers are 8mm long and 13μm in diameter, and the PVA fibers are 6mm long and 30μm in diameter, both treated with KH-550 silane coupling agent at a dosage of 1.0% of the total mass of the basalt and PVA fibers.

[0048] The preparation method of this modified concrete is as follows: S1: Mix the calcined coal gangue powder, metakaolin, limestone powder, slag and silicate cement in a forced mixer for 3 minutes to obtain a dry mix; S2: Heat the mixing water to 38°C, add the viscosity modifier and polycarboxylate superplasticizer of the formula amount and stir to dissolve, then add the nano silica sol dispersed by the nano silica dispersant, stir for 2 minutes to obtain the liquid phase system; S3: Add the dry mixture to the liquid phase system and stir for 2 minutes. Then add the steel fiber treated with NDZ-201 and stir for 1.5 minutes. Then add the basalt fiber and PVA fiber treated with KH-550 and stir for 1.5 minutes to obtain the modified concrete mixture. The outlet temperature is 35℃. The NDZ-201 titanate coupling agent treatment process for steel fibers is as follows: The steel fibers are immersed in a 5wt% NaOH aqueous solution and treated at 60℃ for 10 minutes to remove surface oil and oxides; after removal, they are rinsed with water until neutral; then immersed in a 10wt% HCl aqueous solution and activated at room temperature for 5 minutes to expose the fresh metal oxide surface; after removal, they are rinsed with water until neutral and dried at 60℃; the pretreated steel fibers are immersed in an isopropanol solution of NDZ-201 titanate coupling agent (NDZ-201 concentration is 1-3wt%) for 3-5 minutes; after removal, they are dried at 80℃ for 30 minutes to obtain steel fibers treated with NDZ-201. The KH-550 silane coupling agent treatment process for basalt fiber and PVA fiber is as follows: KH-550 silane coupling agent is added to an ethanol-water mixture (ethanol to water volume ratio of 7:3), the pH is adjusted to 3.5-4.5 with dilute acetic acid, and the mixture is stirred and hydrolyzed for 30-60 minutes to obtain KH-550 hydrolysate; basalt fiber is immersed in the above KH-550 hydrolysate for 2-4 minutes; PVA fiber is immersed in the above KH-550 hydrolysate for 1-3 minutes; after removal, it is dried at 80-100℃ for 30-60 minutes to obtain KH-550 treated basalt fiber and PVA fiber respectively.

[0049] The modified concrete is used in the manufacture of cement poles as follows: A1: Preheat the pipe mold to 43℃, and then pour the modified concrete mixture into the pipe mold; A2: Centrifugal molding: Low-speed feeding stage: 100 rpm for 2.5 min (the temperature of the mixture rises from 35℃ to 38℃); Medium-speed compaction stage: 280 rpm for 4 min (the temperature of the mixture rises from 38℃ to 43℃); High-speed finishing stage: 520 rpm for 6 min (the temperature of the mixture stabilizes at 43-45℃). A3: Perform gradient steam curing: static stop stage at 28℃ for 2.5h, heating stage at a rate of 12℃ / h from 30℃ to 65℃, constant temperature stage at 65℃ for 5h, cooling stage at a rate of 8℃ / h to room temperature. A4: Demolding yields cement poles.

[0050] Example 2 The difference between Example 2 and Example 1 is that the molar content of 2-acrylamide-2-methylpropanesulfonic acid in the viscosity modifier is 10%, and the amount of viscosity modifier used is 4 parts. Other components, formulations, and process parameters are the same as in Example 1.

[0051] Example 3 The difference between Example 3 and Example 1 is that the molar content of 2-acrylamide-2-methylpropanesulfonic acid in the viscosity modifier is 20%, and the amount of viscosity modifier used is 4 parts. Other components, formulations, and process parameters are the same as in Example 1.

[0052] Example 4 The difference between Example 4 and Example 1 is that the amount of viscosity modifier used is 3 parts. Other components, formulations, and process parameters are the same as in Example 1.

[0053] Example 5 The difference between Example 5 and Example 1 is that the amount of viscosity modifier used is 8 parts. Other components, formulations, and process parameters are the same as in Example 1.

[0054] Example 6 The difference between Example 6 and Example 1 is that the constant temperature for steam curing is 60°C and the constant temperature time is 6 hours. Other components, formulations, and process parameters are the same as in Example 1.

[0055] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the viscosity modifier was replaced by a composite system of hydroxyethyl cellulose (HEC) and vegan gum (2 parts HEC + 2 parts vegan gum, totaling 4 parts), while the other components, formulation and process parameters were the same as in Example 1.

[0056] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the viscosity modifier was replaced by N-isopropylacrylamide homopolymer (PNIPAM, 4 parts) instead of P(NIPAM-co-AMPS) copolymer. The other components, formulation and process parameters were the same as in Example 1.

[0057] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the mixing water temperature is room temperature (20-25℃), the mold is not preheated (room temperature), and other components, formulations, and process parameters are the same as in Example 1. This comparative example is used to compare whether a temperature-sensitive phase change can be reliably triggered under conditions without a temperature preset.

[0058] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that only 24 parts of steel fiber were used in the fiber material, and basalt fiber and PVA fiber were removed. Other components, formulations and process parameters were the same as in Example 1.

[0059] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that steam curing was changed to room temperature curing (20°C, 24h), while the other components, formulations and process parameters were the same as in Example 1.

[0060] Comparative Example 6 The difference between Comparative Example 6 and Example 1 is that the fiber coupling treatment was changed to uniformly using KH-550 silane coupling agent to treat the three types of fibers (KH-550 dosage is 1.0% of the total fiber mass), while other components, formulations and process parameters are the same as in Example 1.

[0061] Comparative Example 7 The difference between Comparative Example 7 and Example 1 is that centrifugal molding was replaced with vibration molding (vibration frequency 50Hz, time 3min), while other components, formulations and process parameters are the same as in Example 1.

[0062] Comparative Example 8 The difference between Comparative Example 8 and Example 1 is that the prestressed tailings concrete pole formula and process disclosed in Chinese Patent CN121248257A (using modified iron tailings as the main aggregate, combined with various mineral admixtures and fiber materials, using a hydroxyethyl cellulose and venetian gum composite system as a viscosity modifier, and employing vibration molding and room temperature curing) is adopted, and other parameters are performed according to the content disclosed in the patent.

[0063] The modified concrete and cement poles prepared in Examples 1-6 and Comparative Examples 1-8 were subjected to performance tests. The test items and standards are as follows: (1) The pressure bleeding rate test of concrete mixture shall be carried out in accordance with the method specified in Chapter 13 of GB / T 50080-2016 "Standard for Test Methods of Performance of Ordinary Concrete Mixture"; (2) The cube compressive strength test shall be carried out in accordance with the method specified in Chapter 5 of GB / T 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete", and the standard curing shall be carried out for 28 days. (3) Flexural strength test shall be conducted in accordance with the method specified in Chapter 10 of GB / T 50081-2019, using three-point loading; (4) The flexural toughness index test shall be conducted according to the toughness index method specified in Appendix C of JGJ / T 221-2010 "Technical Specification for Application of Fiber Reinforced Concrete"; (5) The water permeability test shall be conducted according to the stepwise pressure method specified in Chapter 4 of GB / T 50082-2024 "Standard for Test Methods of Long-term Performance and Durability of Concrete"; (6) Freeze resistance test shall be conducted according to the rapid freezing method specified in Chapter 5 of GB / T 50082-2024; (7) The bending moment test for crack resistance of cement poles shall be carried out in accordance with the cantilever test method specified in Appendix B of GB / T 4623-2014 (or GB / T 4623-2025) "Circular Concrete Poles".

[0064] The test results for each embodiment and comparative example are shown in Table 1 below.

[0065] Table 1 Performance test results of the examples and comparative examples Experimental conclusion: As can be seen from the data in Table 1: The pressure bleeding rate of the modified concrete in Examples 1-6 was 9.8%-14.5%, significantly lower than that of Comparative Examples 1-8 (15.5%-32.5%), with Comparative Example 3 (without temperature pre-setting) having a pressure bleeding rate as high as 32.5%. This result indicates that the present invention, using P(NIPAM-co-AMPS) copolymer as a viscosity modifier and combined with a temperature control process (mixing water temperature 35-40 ℃, mold preheating 40-45 ℃), can effectively trigger a thermosensitive phase transition during centrifugal molding, significantly suppressing stratification and fiber sedimentation of the mixture.

[0066] The 28-day cubic compressive strength of Examples 1-6 was 76.8-82.5 MPa, the flexural strength was 13.2-14.2 MPa, and the flexural toughness index I5 was 5.5-6.2, all significantly better than the comparative examples. Among them, Comparative Example 4 (using only a single steel fiber), although having a decent compressive strength (80.5 MPa), had significantly lower flexural strength and toughness index than the examples, indicating that the three-scale hybrid reinforcement system of steel fiber / basalt fiber / PVA fiber of the present invention can effectively leverage the bridging and toughening effects of each fiber at different scales.

[0067] Examples 1-6 show that the water penetration resistance level reaches P10-P12 and the freeze resistance level (rapid freezing method) reaches F200-F300, demonstrating the significant optimization effect of the multi-element active mineral admixture system of the present invention on the matrix density.

[0068] The crack resistance test bending moments of the Φ190 mm × 12 m non-prestressed tapered poles prepared in Examples 1-6 ranged from 20.2 to 22.5 kN·m, all meeting the corresponding requirements of GB / T 4623. However, the crack resistance test bending moments of Comparative Examples 1, 2, 3, and 7 were 16.5 kN·m, 15.2 kN·m, 13.5 kN·m, and 16.0 kN·m, respectively, all failing to meet the standard requirements. These results validate the synergistic technical effects of the temperature-sensitive adhesion enhancement, multi-scale fiber reinforcement, and centrifugal molding process of this invention at the pole product level.

[0069] In summary, the modified concrete, its preparation method, and its application provided by this invention have achieved significant technical effects in suppressing segregation, improving mechanical properties, and enhancing durability.

[0070] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit them. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A modified concrete, characterized in that, Based on parts by weight, it includes the following components: 350-450 parts silicate cement, 200-280 parts calcined coal gangue powder, 150-220 parts metakaolin, 15-25 parts nano silica sol, 120-180 parts limestone powder, 400-500 parts slag, 0.1-0.5 parts nano silica dispersant, 3-8 parts viscosity modifier, 17-33 parts fiber material, 5-10 parts polycarboxylate superplasticizer, and 342-571 parts mixing water; The viscosity modifier is a copolymer of N-isopropylacrylamide and 2-acrylamide-2-methylpropanesulfonic acid, wherein the molar content of 2-acrylamide-2-methylpropanesulfonic acid is 10%-20%. The method for preparing the modified concrete includes: The calcined coal gangue powder, metakaolin, limestone powder, slag and silicate cement in the formula are thoroughly mixed to obtain dry mix; The viscosity modifier, polycarboxylate superplasticizer, and mixing water were mixed in the specified amounts, and nano-silica sol dispersed by nano-silica dispersant was added to obtain a liquid phase system. The dry mixture is added to the liquid system and stirred. Fiber materials are added in batches and stirring is continued to obtain a modified concrete mixture. The temperature of the mixing water is controlled at 35-40℃, and the outlet temperature of the modified concrete mixture is controlled at 32-36℃.

2. The modified concrete as described in claim 1, characterized in that, The fiber material comprises 12-20 parts steel fiber, 3-8 parts basalt fiber and 2-5 parts PVA fiber; The steel fibers have a length of 8-12 mm and a diameter of 0.15-0.20 mm; the basalt fibers have a length of 6-12 mm and a diameter of 10-17 μm; and the PVA fibers have a length of 4-8 mm and a diameter of 20-40 μm.

3. The modified concrete as described in claim 2, characterized in that, The steel fiber is a steel fiber treated with NDZ-201 titanate coupling agent, and the amount of NDZ-201 titanate coupling agent is 0.3-0.8% of the mass of the steel fiber; The basalt fiber and PVA fiber are basalt fiber and PVA fiber treated with KH-550 silane coupling agent, respectively, and the amount of KH-550 silane coupling agent is 0.8-1.5% of the total mass of basalt fiber and PVA fiber.

4. The modified concrete as described in claim 1, characterized in that, The silica particles in the nano silica sol have a diameter of 20-50 nm and a solid content of 20-30 wt%.

5. The modified concrete as described in claim 1, characterized in that, The calcined coal gangue powder is calcined coal gangue powder that has been impregnated with 5-10wt% dilute sulfuric acid for 2-4 hours, washed with water until neutral, and then dried.

6. The application of modified concrete as described in any one of claims 1-5 in the manufacture of cement poles, characterized in that, include: The modified concrete mixture is fed into a preheated pipe mold at a temperature of 40-45°C. The tube mold is centrifuged and formed; After centrifugal molding, the material is steam cured and then demolded to obtain cement poles.

7. The application according to claim 6, characterized in that, The centrifugal forming process employs a three-stage centrifugal forming method, comprising, in sequence: During the low-speed fabric feeding stage, the rotation speed is 80-120 rpm and the time is 2-3 minutes; During the medium-speed compaction stage, the rotation speed is 200-350 rpm and the time is 3-5 minutes; During the high-speed finishing stage, the rotation speed is 450-600 rpm and the time is 5-8 minutes.

8. The application according to claim 6, characterized in that, The steam curing includes: After standing at 25-30℃ for 2-3 hours, the temperature is increased from 30℃ to 60-70℃ at a rate of 10-15℃ / h. Steam curing is carried out at a constant temperature of 60-70℃ for 4-6 hours, and then cooled down from 60-70℃ to room temperature at a cooling rate of no more than 10℃ / h to complete the steam curing.

Citation Information

Patent Citations

  • Prestressed tailing concrete pole and manufacturing method thereof

    CN121248257A

  • Tensile and anti-crack type concrete electric pole

    CN121292904A

  • Emulsion polymerized cement suspension agent

    WO2020005255A1